Efficacy and Tolerability of the Combination Valsartan/Hydrochlorothiazide Compared with Amlodipine in a Mild-to-moderately Hypertensive Brazilian Population - Franco, Roberto J.S. [UNESP]; Goldflus, Suely; McQuitty, Mari; Oigman, Wille (Taylor & Francis, 2003)
Most hypertensive patients need more than one drug to reach recommended blood-pressure targets. We investigated the effects on 24-h ambulatory blood pressure (ABP) of the angiotensin-receptor blocker, valsartan, in combination with hydrochlorothiazide (HCTZ), compared with the calcium-channel blocker amlodipine in a Brazilian population in a multicentre, double-blind, double-dummy, parallel group, controlled study in 373 patients with essential hypertension. After a 2-week washout period, patients with a mean sitting systolic blood pressure (SBP) of 160-190 mmHg were randomized to receive either valsartan 160 mg o.d., or amlodipine 5 mg o.d. for 2 weeks and subsequently force-titrated to valsartan 160 mg/HCTZ 25 mg o.d. or amlodipine 10 mg o.d. This regimen was continued until the end of the study at week 8. The primary efficacy parameter was the change from baseline to week 8 in mean 24-h SBP. Secondary endpoints were change in mean 24-h diastolic blood pressure (DBP), tolerability and safety of treatments. Valsartan/HCTZ achieved a mean reduction in systolic ABP of -19.1 ± 11.3 mmHg compared with -20.7 ± 12.0 mmHg with amlodipine (p = 0.324 for the comparison) and in diastolic ABP by -11.1 ± 7.4 mmHg vs -11.6 ± 7.2 mmHg by amlodipine (p = 0.853 for the comparison). The valsartan/HCTZ group exhibited markedly lower rates of adverse events and discontinuations than the amlodipine group. Peripheral oedemas were far more frequent with amlodipine than with valsartan/HCTZ (1.6% with valsartan/HCTZ; 16.8% with amlodipine). Thus, the valsartan 160 mg/HCTZ 25 mg combination appears to be as efficacious as amlodipine 10 mg in this patient population but better tolerated.
Keywords: Angiotensin-receptor blocker; Calcium-channel blocker; Combination therapy; Ethnicity; Hypertension; amlodipine; creatinine; hydrochlorothiazide; valsartan; drug derivative; tetrazole derivative; valine; adult; aged; antihypertensive therapy; blood pressure monitoring; blood pressure regulation; Brazil; clinical trial; controlled clinical trial; controlled study; creatinine blood level; diastolic blood pressure; disease severity; dizziness; double blind procedure; drug efficacy; drug safety; drug tolerability; essential hypertension; female; headache; heart palpitation; human; major clinical study; male; multicenter study; peripheral edema; priority journal; randomized controlled trial; side effect; blood pressure; chemically induced disorder; comparative study; drug combination; drug effect; edema; ethnology; hypertension; middle aged; race; treatment outcome; Aged; Amlodipine; Blood Pressure; Blood Pressure Monitoring, Ambulatory; Continental Population Groups; Double-Blind Method; Drug Therapy, Combination; Edema; Female; Humans; Hydrochlorothiazide; Male; Middle Aged; Tetrazoles; Treatment Outcome; Valine